2015
DOI: 10.1074/jbc.m115.646208
|View full text |Cite
|
Sign up to set email alerts
|

Increased NF-κB Activity and Decreased Wnt/β-Catenin Signaling Mediate Reduced Osteoblast Differentiation and Function in ΔF508 Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Mice

Abstract: Background:We analyzed the mechanisms mediating osteoblast dysfunctions in cystic fibrosis. Results: Osteoblast differentiation and function are impaired in ⌬F508-CFTR mice due to overactive NF-B and reduced Wnt/␤-catenin signaling. Correcting these pathways rescued the defective osteoblast functions. Conclusion: Osteoblast dysfunctions in ⌬F508-CFTR mice result from altered NF-B and Wnt/␤-catenin signaling. Significance: Targeting the altered signaling pathways can restore osteoblast functions in cystic fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 46 publications
2
24
1
1
Order By: Relevance
“…Previous studies have implicated -catenin in the stabilization and cytoplasmic sequestration of p65NFB [32]. Wnt/ -catenin signalling plays a role in the regulation of osteoclast and osteoblast differentiation, and Sclerostin, a secreted inhibitor of Wnt/ -catenin signalling reduces bone formation [25][26][27]32]. In broad agreement with these findings, we showed that NFB inhibition by PTN in osteoblasts and osteoclasts was accompanied by a significant increase in -catenin activation and expression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have implicated -catenin in the stabilization and cytoplasmic sequestration of p65NFB [32]. Wnt/ -catenin signalling plays a role in the regulation of osteoclast and osteoblast differentiation, and Sclerostin, a secreted inhibitor of Wnt/ -catenin signalling reduces bone formation [25][26][27]32]. In broad agreement with these findings, we showed that NFB inhibition by PTN in osteoblasts and osteoclasts was accompanied by a significant increase in -catenin activation and expression.…”
Section: Discussionsupporting
confidence: 90%
“…There is also evidence to suggest that NFB regulates osteoclast and osteoblast activity through its crosstalk with the Wnt/ -catenin pathway [23]. In osteoblasts, activation of -catenin stimulates bone formation and enhances the expression of runt related transcription factor 2 (Runx2), a key osteogenic factor essential for osteoblast differentiation [24][25][26][27]. Activation of -catenin inhibits osteoclast formation [28][29][30] and activation of NFB by RANKL in osteoclasts leads to -catenin inhibition [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our results, these studies also found increased β-catenin phosphorylation, reduced osteoblast β-catenin expression and altered expression of Wnt/β-catenin target genes in ΔF508 mutant osteoblasts. 39,40 Given that bone is of mesoderm origin, it is plausible that the defected mesoderm differentiation reported in our study contributes to the pathological condition of bone in ΔF508 mice. Collectively, in view of the importance of Wnt/β-catenin pathway in embryonic development, the presently demonstrated critical role of CFTR in regulating β-catenin signaling provides novel insights into the molecular mechanism underlying embryonic development.…”
Section: Discussionmentioning
confidence: 83%
“…Of the identified 1,900 mutations of CFTR in humans, deletion of the phenylalanine at position 508 (DF508) is the most frequent mutation found in CF patients, which results in a folding defect and endoplasmic reticulum associated degradation of CFTR [17]. It is being recently recognized that apart from transporting anions, CFTR is involved in other cellular functions, including inflammation [6,18], proliferation [19][20][21], and differentiation [22][23][24] in bronchial epithelia, granulosa cells, enterocytes, and osteoblasts. Several signaling molecules associated with CFTR have been reported, including MAPK and NF-κB [6,18,[25][26][27][28].…”
mentioning
confidence: 99%